2003
DOI: 10.1080/1475636031000093543
|View full text |Cite
|
Sign up to set email alerts
|

New Ursolic and Betulinic Derivatives as Potential Cytotoxic Agents

Abstract: Fifteen new ursolic and betulinic triterpenoids, bearing various functionalities at C-3 and C-28 were synthesized as potential cytotoxic agents. All compounds were obtained by a hemisynthetic route via ursolic and betulinic acids. Preliminary screening of these compounds on human HT 29 colon cancer cells revealed inhibitory activity for three of them. Beta-D-Glucopyranosyl-3beta-hydroxyurs-12(13)-en-28-oate 1c, 3beta-3-(3-pyridyl)-prop-2-enoyloxyurs-12(13)-en-28-oic acid 1i and the potassium salt of 3beta-cinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
2
11
0
3
Order By: Relevance
“…Moreover, Mullauer et al (2009) recently showed that the in vitro cytotoxic activity of betulin (2) is significantly enhanced in the presence of cholesterol. Betulinic acid (3), which features a carboxylic acid at the C-28 position, is definitely the most studied member of the so-called lupane-type triterpenoids (Baglin et al 2003b;Bi et al 2005;Cichewicz and Kouzi 2004;Eiznhamer and Xu 2004;Mukherjee et al 2006;Ovesná et al 2004;Yogeeswari and Sriram 2005). The biological activity of more than 2,500 plant species is due to the presence of betulinic acid (3) (Baglin et al 2003b;Eiznhamer and Xu 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Moreover, Mullauer et al (2009) recently showed that the in vitro cytotoxic activity of betulin (2) is significantly enhanced in the presence of cholesterol. Betulinic acid (3), which features a carboxylic acid at the C-28 position, is definitely the most studied member of the so-called lupane-type triterpenoids (Baglin et al 2003b;Bi et al 2005;Cichewicz and Kouzi 2004;Eiznhamer and Xu 2004;Mukherjee et al 2006;Ovesná et al 2004;Yogeeswari and Sriram 2005). The biological activity of more than 2,500 plant species is due to the presence of betulinic acid (3) (Baglin et al 2003b;Eiznhamer and Xu 2004).…”
Section: Introductionmentioning
confidence: 96%
“…Modifications of the parent structure of these compounds at these positions can produce potentially important derivatives, found to be more effective than the starting ones, thus making them appealing for further development as antitumour drugs. 18,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Nitrogen-containing derivatives of 1 and 2, such as Betulin 1: R = CH 2 OH Betulinic acid 2: R = COOH amine derivatives, 21,23,35 oxime derivatives, 21,23,30 amino acid conjugates, 22 amide derivatives, 20,32 hydrazine 29 and hydrazone derivatives, [28][29][30]35 imidazolide derivatives, 37 and other N-heterocyclic derivatives 24,31,34,36 have been reported to possess antiproliferative effect against tumour cell lines.…”
Section: Introductionmentioning
confidence: 99%
“…Cette méthodologie qui mène à la formation de 1,2-frans-grycosides dans de hauts rendements implique l'utilisation de sucres bromes peracétylés en présence d'un agent catalyseur de transfert de phase (Aliquat 336) dans une solution hétérogène de Figure 40) [Baglin et al, 2003b]. La saponine obtenue avec un rendement élevé (92%) n'a pas exercé d'activité cytotoxique à la plus haute concentration testée (IC50 >500 uM).…”
Section: Autres Groupesunclassified